2015
DOI: 10.1021/acs.jpcb.5b00741
|View full text |Cite
|
Sign up to set email alerts
|

Particle and Energy Pair and Triplet Correlations in Liquids and Liquid Mixtures from Experiment and Simulation

Abstract: Recent advances in fluctuation solution theory (FST) have provided access to information concerning triplet fluctuations and integrals, in addition to the established pair fluctuations and integrals, for liquids and liquid mixtures using both experimental and simulation data. Here, FST is used to investigate pair and triplet correlations for (i) pure water as provided by experiment and simulation using both polarizable and nonpolarizable water models, (ii) liquid mixtures of methanol and water as provided by e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(33 citation statements)
references
References 89 publications
1
32
0
Order By: Relevance
“…First, the general questions beyond the conventional pair approaches: (a) effects on the thermodynamic properties; 1,14,15 (b) the connections with the density (or pressure) derivatives of the radial and Fourier pair structures of fluids (i.e., g 2 (r), r = |r 1 − r 2 | ; S (2) (k), k = |k|); 1,[16][17][18][19][20] and (c) the characterization of fluid mixtures. [21][22][23] Second, multiple scattering 1,24 and the early studies of excitations in helium II. 25,26 Third, the density functional theories of freezing, [27][28][29][30] the theories of glass-forming liquids, 6,31 and the large variety of interfacial phenomena.…”
Section: Introductionmentioning
confidence: 99%
“…First, the general questions beyond the conventional pair approaches: (a) effects on the thermodynamic properties; 1,14,15 (b) the connections with the density (or pressure) derivatives of the radial and Fourier pair structures of fluids (i.e., g 2 (r), r = |r 1 − r 2 | ; S (2) (k), k = |k|); 1,[16][17][18][19][20] and (c) the characterization of fluid mixtures. [21][22][23] Second, multiple scattering 1,24 and the early studies of excitations in helium II. 25,26 Third, the density functional theories of freezing, [27][28][29][30] the theories of glass-forming liquids, 6,31 and the large variety of interfacial phenomena.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, previous studies have shown that the GCE distributions are not Gaussian (or symmetric) and therefore this assumption is not justified for the present purposes. 14,20 This point will also be discussed further in Sec. III.…”
Section: Ds/rmentioning
confidence: 85%
“…Hence, the excess entropy and enthalpy fluctuations are equal and therefore δS E could be used in place of δH E in the following equations. If we substitute the expressions for δE and δV given by Equation (20) into the expression for S (2) found in Equation (5) and then collect identical terms the result can be written as…”
Section: A Gaussian Distributionsmentioning
confidence: 99%
See 2 more Smart Citations